Genetic and epigenetic factors in the regulation of the immune response. Issue 3 (June 2016) - Dahmer, Mary K.; Cornell, Timothy; Quasney, Michael W.
Abstract : Purpose of review: The review will update readers on research examining the influence of genetic variation and epigenetics on the immune system and whether genetic variation influences the outcome of critically ill children. Recent findings: Although there have been few recent studies examining the role of genetic variation in the severity of disease or outcome in critically ill children, studies in critically ill adults have been informative. For example, genetic variations in the genes coding for various components of the immune response, such as the Toll-like receptor 1, interleukin-1RA, proprotein convertase subtilisin/kexin type 9, adoponectin, nuclear factor erythroid 2–related factor 2, elafin, sphingosine 1-phosphate receptor 3, and sushi, von Willebrand factor type A, EGF and pentraxin domain containing 1 have been associated with various outcomes in critically ill adult populations. Many of the variants demonstrate functional consequences in the protein levels or activities. In critically ill children, there is an association with increased ICU length of stay in children with septic shock with one of the Toll-like receptor 1 variants. Summary: The degree of influence of host genetic variation in the outcome in critically ill children remains a much understudied area of research. However, it remains important because it may not only help identify children at risk for worse outcomes but it may provide insight into mechanisms of critical illnesses and novel therapies.